Exploiting the Irish border to estimate minimum wage impacts in Northern Ireland - Duncan McVicar; Andrew Park; Séamus McGuinness (IZA Journal of Labor Economics, 2019)
This paper examines the impacts of the introduction of the UK National Minimum Wage (NMW) in 1999 and the introduction of the UK National Living Wage (NLW) in 2016 in Northern Ireland (NI) on employment and hours. NI is the only part of the UK with a land border where the NMW and NLW cover those working on one side of the border but not those working on the other side of the border (i.e., Republic of Ireland). This discontinuity in minimum wage coverage enables a research design that estimates the impacts of the NMW and NLW on employment and hours worked using difference-in-differences estimation. We find a small decrease in the employment rate of 22-59/64-year-olds in NI, of up to 2% points, in the year following the introduction of the NMW, but no impact on hours worked. We find no clear evidence that the introduction of the NLW impacted either employment or hours worked in NI.
Keywords: E24; J31; J38; 330; minimum wages; Northern Ireland; employment; hours